Algebra and Trigonometry 10th Edition

Published by Cengage Learning
ISBN 10: 9781337271172
ISBN 13: 978-1-33727-117-2

Chapter 1 - 1.1 - Graphs of Equations - 1.1 Exercises - Page 79: 62



Work Step by Step

$(x-h)^2+(y-k)^2=r^2$ $h=1$, $k=-3$ and $r=\sqrt {11}$: $(x-1)^2+[y-(-3)]^2=(\sqrt {11})^2$ $(x-1)^2+(y+3)^2=11$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.